CONSEQUENCES OF LEADING HEALTH LIFESTYLE ON LIPID PROFILE - Aziz, Nafi; Hussein, Saad; Farhood, Israa Kadhum; Aziz, Noor Nafi (PT. Antis International Publisher, 2024)
The activity of improving and promoting health is through leading proper health behavior which includes perfect and suitable methods for health living; through leading health lifestyle; via periodic medical consultations and attending physicians for medical checkup and advice. Beside choosing balanced diet and encourage sport exercises; cessation of smoking and alcohol intake. The other aspect, that results in promoting health, longevity and quality of living through preventing of disease occurrence should be through clinical and physical examination via screening services of diseases, such as ischemic heart disease, hypertension and renal problems. All these personal activities will lead to health lifestyle, which consequently is going to minimize the diseases might occur. On conclusion, the study shows that these behavioral aspects will reduce lipid profile; blood pressure, body weight and increase physical fitness in 42% of cases and border line effect on outcome is approximately about 58% of cases and the variable that plays a role is socio – economic status